PROFIL SOSIAL EKONOMI MASYARAKAT DI DESA MAILEPPET KECAMATAN SIBERUT SELATAN KABUPATEN KEPULAUAN MENTAWAI - Rahayu, RidaCintia; Rianto, Slamet; Nefilinda, Nefilinda (STKIP PGRI Sumbar, 2013)
This research is a qualitative study with interview techniques. To answer this problem used primary data and secondary data. Primary data was collected through observation, interviews, discussions with the local community and the photographs taken in the field, while the secondary data obtained from the relevant parties. This study aimed to obtain information, analyze and describe data on: (1) social custom in the village Maileppet, (2) the level of income of the people in the village Maileppet and (3) Education Level Maileppet community in the village. Research results showed: (1) in the Village Peoples habits including good Maileppet, people in the village Maileppet still often worked together, especially in the wedding ceremony and took a boat out to sea from the hills. Societys view of the development also includes either because people are very concerned about the development programs undertaken in the village Maileppet (2) The level of income of the people in the village Maileppet, generally people Maileppet worked as a farmer, but the public generally has a side job. Income varies between Rp 500,000 - Rp 1.000.000/bulan and income from side jobs between Rp 200,000 - Rp 500.000/bulan. Income from such work can meet the needs of the family (3) The level of public education in the village Maileppet generally low, the average graduate junior high, public education is generally completed at the age of 15 years.